EFFECTIVENESS OF PUZZLE EDUCATIVE GAME TOOLSON MOTOR DEVELOPMENT IN 6-YEAR-OLD CHILDRENAT KINDERGARTEN SANTA MARIA PARE, KEDIRI DISTRICT - Astri Yunita; Liya Ni’matul Maula; Erni Rahmawati; Dily Ekasari (Suluh Adiluhung Publisher (SAPub), 2024)
Training the development of fine motor skills is very important, so activities are needed that can help in the process of developing children's fine motor skills. Delays in fine motor development will have an impact on subsequent development, where there are long-term negative impacts for children who experience delays in basic motor development. The aim of this research was to determine the effectiveness of educational puzzle games on fine motor development in children aged 6 years. The research design is pre-experimental with a one group pretest - posttest design. The population was all 6-year-old children in Kindergarten Santa Maria, Pare District, Kediri Regency, East Java, totaling 92 children, a sample of 48 respondents using a purposive sampling technique. The data collection technique uses a questionnaire. Data analysis used the Wilcoxon test with the p value < α, α:0.05. The results of the research showed that before the treatment, almost all respondents had questionable fine motor development, namely 39 respondents (81.2%), whereas after treatment, almost all respondents had appropriate fine motor development, namely 45 respondents (93.8%). %). Results of data analysis sig value (2-tailed): 0.001. Educational puzzle game therapy influences fine motor development in children aged 6 years. Routine activities to stimulate the development of fine motor skills can improve the fine motor development of pre-school aged children, one of which is using educational puzzle games so that they can run optimally.